Generational differences in the workplace : Performance optimization - Zabolotný, Samuel; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The purpose of this thesis is to examine the differences in work performance between single-generation and multigenerational teams, providing management with alternative strategies for performance optimization. Currently, no specific study directly compares the productivity of generational teams. Therefore, this paper synthesizes existing literature to establish a foundation for further research. Key concepts and terminology are contextualized to ensure a comprehensive understanding of the issue and its contemporary relevance. Given the absence of a universal performance metric, the study explores various sources to illustrate the complexity of workplace productivity. The research also identifies limitations and opportunities for future exploration, with potential applications in management and strategic consultancy to enhance workforce efficiency.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses